Microhabitat level thermal physiology and thermoregulation of a diurnal gecko in an urban landscape - Apte, Vaishnavi; Tatu, Avichal; Thaker, Maria (Frontiers in Amphibian and Reptile Science, 2025)
Urban areas comprise a matrix of natural and human-made microhabitats, with associated variation in microclimates. Since reptiles are dependent on environmental temperature for optimal functioning, their survival in cities depends on how well they can navigate microhabitat-level thermal heterogeneity. For the Mysore Day gecko (Cnemaspis mysoriensis) in the urban environment of Bengaluru, we determined if shifts in thermal physiology or behavioural thermoregulatory strategies were used to adapt to human-made microhabitats (e.g. walls) compared to natural microhabitats (tree trunks and roots). We collected active body temperatures and environmental temperatures in the field, and measured preferred temperature (Tset), thermal tolerance limits (CTmax and CTmin), and thermal performance curve (TPC) of locomotion in the lab. We found that human-made microhabitats had slightly higher and more variable environmental temperatures than the natural microhabitats. Thermal physiological variables (Tset, CTmax, CTmin, and TPC) of lizards caught from these distinct microhabitats did not vary, implying a conserved thermal physiology within the species. However, given the body temperatures of lizards in the wild, natural microhabitats seem to be of better thermal quality, providing a suitable temperature range that is closer to preferred temperatures for the species. Hence, in natural spaces, lizards can thermoregulate more accurately. We demonstrate that even small differences in thermal conditions at the microhabitat scale can influence accuracy of thermoregulation for lizards in the city. Our result emphasise the importance of retaining natural habitats in a cityscape for effective thermoregulation of small ectotherms, like C. mysoriensis.